Refined fluorescent STR quantification of cell-free fetal DNA during pregnancy in physiological and Down syndrome fetuses - Vodicka, Radek; Vrtel, Radek; Dusek, Ladislav; Prochazka, Martin; Schneiderova, Eva; Vrbicka, Dita; Krejcirikova, Eva; Dhaifalah, Ishraq; Santava, Alena; Santavy, Jiri (Prenatal diagnosis, 2008)
BACKGROUND: Cell-free fetal (cff) DNA analysis by short tandem repeats (STR) has the advantage of better recognizing the different genotypes. However, quantitative examination by quantitative fluorescent (QF) polymerase chain reaction (PCR) by STRs is limited to only a rough approximation. This project focuses on a more precise calculation of the relative cff DNA amount tested in the STRs' loci. METHODS: The cff DNA was analyzed in 363 samples from 258 pregnant women with physiological fetuses in different stages of pregnancy (from 4-37 gestational weeks) separately in three STRs [D21S1435, D21S1446 and PentaD (pD)] and also by gonosomal sequences amelogenin gene, X/Y-linked/testis specific protein, Y-linked (AMELX/Y/TSPY). Seventeen samples of cff DNA from fetuses with Down syndrome (DS) were compared. We optimized the refined quantitative fluorescent (RQF) PCR for STRs in a particular locus. RESULTS AND CONCLUSIONS: The cff DNA detection rate was 74% in at least one of the STRs. The efficiency decreased from shorter to longer PCR fragments. All three STR and gonosomal loci proved an increase in cff DNA during pregnancy. The stutter variability rate is greatest in short STR fragments and decreases as the STR fragments increase in length. Results showed that DS samples had a significantly higher amount of cff DNA.
Keywords: Fetomaternal Transfusion; Microsatellite Repeats; Prenatal Diagnosis; mikrosatelitní repetice; Downův syndrom; DNA; Female; Pregnancy; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; prenatální diagnóza; Down Syndrome; fetomaternální transfuze; těhotenství